The Distributional Impact of Recessions : the Global Financial Crisis and the Pandemic Recession - Shibata, Ippei (IMF Working Papers; Working Paper, 2020)
Using the U.S. Current Population Survey data, this paper compares the distributional impacts of the Pandemic Crisis and those of the Global Financial Crisis in terms of (i) worker characteristics, (ii) job characteristics-'social' (where individuals interact to consume goods), 'teleworkable' (where individuals have the option of working at home), and 'essential' jobs (which were not subject to government mandated shut-downs during the recent recession), and (iii) wage distributions. We find that young and less educated workers have always been affected more in recessions, while women and Hispanics were more severely affected during the Pandemic Recession. Surprisingly, teleworkable, social and essential jobs have been historically less cyclical. This historical acyclicality of teleworkable occupations is attributable to its higher share of skilled workers. Unlike during the Global Financial Crisis, however, employment in social industries fell more whereas employment in teleworkable and essential jobs fell less during the Pandemic Crisis. Lastly, during both recessions, workers at low-income earnings have suffered more than top-income earners, suggesting a significant distributional impact of the two recessions.